Gaia DR1 evidence of disrupting the perseus arm - Baba, Junichi; Kawata, Daisuke; Matsunaga, Noriyuki; Grand, Robert J. J.; Hunt, Jason A. S. (The astrophysical journal. Part 2, Letters, 2018)
We have discovered a clear sign of the disruption phase of the Perseus arm in the Milky Way using Cepheid variables, taking advantage of the accurately measured distances of Cepheids and the proper motions from Gaia Data Release 1. Both the Galactocentric radial and rotation velocities of 77 Cepheids within 1.5 kpc of the Perseus arm are correlated with their distances from the locus of the Perseus arm, as the trailing side is rotating faster and moving inward compared to the leading side. We also found a negative vertex deviation for the Cepheids on the trailing side, −27.°6 ± 2.°4, in contrast to the positive vertex deviation in the solar neighborhood. This is, to our knowledge, the first direct evidence that the vertex deviation around the Perseus arm is affected by the spiral arm. We compared these observational trends with our N -body/hydrodynamics simulations based on a static density-wave spiral scenario and with those based on a transient dynamic spiral scenario. Although our comparisons are limited to qualitative trends, they strongly favor the conclusion that the Perseus arm is in the disruption phase of a transient arm.
Gesehen am 15.02.2019